Distributional Consequences of Political Representation - Nicola Maaser; Thomas Stratmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We investigate the geographical concentration of representatives and the distribution of fiscal transfers both theoretically and empirically. We develop a model which predicts that funds to an area are positively correlated with the number of representatives residing in that area. Our empirical analysis uses the fact that due to the electoral rules for German state elections the number of representatives varies quasi-randomly across electoral districts. Controlling for various socio-economic and demographic variables and using a variety of estimation techniques, we find that areas with greater number of representatives receive more government funds.
Keywords: D72; H72; R10; 330